1989 – Personal Reflections on the Year of Revolutions - Reich, Jens (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2009)
AbstractIn a reminiscence of his own participation in the events that led to the fall of the Berlin Wall and the unification of Germany twenty years ago, the author shares his emotion and hopes for the future. His reflection deals with the factors that led to the political transformation of the divided country, such as the accessibility, in Eastern Germany, of televised images of the kind of material abundance available to the Westerners. The author proposes a balance sheet of the long-term effect of events of 1989 for Germany and its inhabitants, as well as for Europe as a whole.